Integrasi Kepemimpinan dan Kompetensi Profesional dalam Mata Kuliah Strategi Pembelajaran PAK: (Studi pada Mahasiswa S1 Pendidikan Agama Kristen) - Kezia Verena; Joshua Christian (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the integration of pedagogical leadership and professional competence in the Christian Religious Education (CRE) learning strategy course among undergraduate students. Employing a quantitative approach with a descriptive-correlational survey design, the research involved 26 respondents. Data were collected using a Likert-scale questionnaire, with the results analyzed using descriptive statistics and Pearson correlation. The findings show that both pedagogical leadership (85%) and professional competence (86%) are categorized as high. The Pearson correlation test reveals a strong and significant relationship between the two variables (r = 0.78). These results suggest that pedagogical leadership and professional competence are effectively integrated in the learning process. The course plays a strategic role in shaping students into professional and reflective learning leaders, providing them with the necessary skills to apply their leadership in educational settings. This integration enhances students' readiness to excel in their future roles, emphasizing the importance of these competencies for becoming well-rounded and effective educators.